Early Childhood Education (PAUD) Class Management at Islamic Kindergarten (RA) Al-Islamiyah - Dermawan, Oki; Kardinah, N; Iqbal, Ahmad; Handayani, Nila Wahyu (Universitas Islam Negeri Raden Intan Lampung, 2023)
Teachers play an essential role in managing the class. Actions that need to be taken by the teacher in creating classroom conditions are communication and interpersonal relationships between students and teachers reciprocally and effectively, arranging classroom equipment and children's seats, and planning or preparing for teaching. This research aims to find out and describe planning in-class management, organizing in-class management, implementing in-class management, and supervising PAUD class management at RA Al-Islamiyah Bandarsakti. The research method used is descriptive analysis, namely data analysis, by emphasizing meaning, reasoning, the definition of certain situations, and describing the behavior of the studied object. Data collection tools used are observation, interviews, and documentation. As for concluding using inductive thinking data, namely thoughts that depart from facts or special events, then conclusions are drawn that have a general nature from these particular facts. The results showed that: class management at RA Al-Islamiyah Bandarsakti. First, classroom management planning has been prepared since the beginning of the learning year, such as making daily lesson plans, weekly lesson plans, semester programs, and making class rules of conduct; Second, in organizing classes, the teacher uses resources according to needs, such as organizing or grouping seats for students and selecting one of the students to dare to lead activities; Third, in the implementation of class management, it is still not optimal in leading, directing, motivating, guiding, being a role model for students in the class both in speech, attitude and way of dressing, as well as the arrangement of infrastructure which is still not optimal; Fourth, in supervising class management the teacher always evaluates learning outcomes every day and then makes comparisons of previous learning outcomes.